2021
DOI: 10.1021/jacs.1c04173
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Fluorescence and the Intramolecular Charge Transfer of Phenothiazine Dipolar and Quadrupolar Derivatives by Oxygen Functionalization

Abstract: A series of new naphthalimide and phenothiazine-based push−pull systems (NPI-PTZ1−5), in which we structurally modulate the oxidation state of the sulfur atom in the thiazine ring, i.e., S(II), S(IV), and S(VI), was designed and synthesized by the Pd-catalyzed Sonogashira cross-coupling reaction. The effect of the sulfur oxidation state on the spectral, photophysical, and electrochemical properties was investigated. The steady-state absorption and emission results show that oxygen functionalization greatly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 56 publications
5
75
1
Order By: Relevance
“…The possible noncovalent interactions between DPP and LGG enable DPP molecules in the supramolecular gel to undergo intramolecular charge transfer, thereby resulting the fluorescence emission. [ 12 ] The excited‐state supramolecular chirality of DPP‐LGG cogel at LGG/DPP = 4:1 can also be measured by circularly polarized luminescence (CPL) spectroscopy (Figure S7, Supporting Information). However, mirror patterns are obtained in CPL spectra, dissymmetry factor values ( g lum ), and CD spectra (Figures S7 and S8, Supporting Information), which indicates the solvent‐induced inversion of supramolecular chirality.…”
Section: Resultsmentioning
confidence: 99%
“…The possible noncovalent interactions between DPP and LGG enable DPP molecules in the supramolecular gel to undergo intramolecular charge transfer, thereby resulting the fluorescence emission. [ 12 ] The excited‐state supramolecular chirality of DPP‐LGG cogel at LGG/DPP = 4:1 can also be measured by circularly polarized luminescence (CPL) spectroscopy (Figure S7, Supporting Information). However, mirror patterns are obtained in CPL spectra, dissymmetry factor values ( g lum ), and CD spectra (Figures S7 and S8, Supporting Information), which indicates the solvent‐induced inversion of supramolecular chirality.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental setup for the femtosecond transient absorption and fluorescence up-conversion measurements has been described elsewhere [ 50 , 51 ]. In particular, a 800-nm radiation is amplified by the Ti:Sapphire laser system (Spectra Physics) and then converted into 400-nm excitation pulses (ca.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] These donor-acceptor (D-A) derivatives exhibit unique photonic properties and that can be improved by simple synthetic changes. 9,10 In these p-conjugated chromophores, the heteroatom-containing cyclic systems were primarily used to tune the photophysical and redox properties of push-pull dyes. Many studies have been reported on developing novel push-pull organic materials for optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported on developing novel push-pull organic materials for optoelectronic applications. 7,[10][11][12][13][14] Our group is interested in the chemistry of phenothiazine. Phenothiazine is a heterocyclic compound with non-planar geometry and a bowl-shaped structure containing electron-rich nitrogen (N) and sulfur (S) heteroatoms.…”
Section: Introductionmentioning
confidence: 99%